Ein neues Konzept für die geberlose Regelung von Permanentmagnet-Synchronmaschinen für Hybrid- und Elektrofahrzeuge (2019)
With the current state of the art angle sensors are used for the operation of permanent magnet synchronous machines in electric and hybrid vehicles. In the present work, a new concept for sensorless control is proposed. The robust operation could be proven with new and further developed sensorless procedures on the machine test bench. The operating range of sensorless control could be significantly increased with the presented methods.